Progression to AIDS in South Africa Is Associated with both Reverting and Compensatory Viral Mutations - Huang, Kuan-Hsiang Gary; Goedhals, Dominique; Carlson, Jonathan M.; Brockman, Mark A.; Mishra, Swati; Brumme, Zabrina L.; Hickling, Stephen; Tang, Christopher S.W.; Miura, Toshiyuki; Seebregts, Chris; Heckerman, David; Ndung'u, Thumbi; et al. (2011)
We lack the understanding of why HIV-infected individuals in South Africa progress to AIDS. We hypothesised that in end-stage disease there is a shifting dynamic between T cell imposed immunity and viral immune escape, which, through both compensatory and reverting viral mutations, results in increased viral fitness, elevated plasma viral loads and disease progression. We explored how T cell responses, viral adaptation and viral fitness inter-relate in South African cohorts recruited from Bloemfontein, the Free State (n = 278) and Durban, KwaZulu-Natal (n = 775). Immune responses were measured by γ-interferon ELISPOT assays. HLA-associated viral polymorphisms were determined using phylogenetically corrected techniques, and viral replication capacity (VRC) was measured by comparing the growth rate of gag-protease recombinant viruses against recombinant NL4-3 viruses. We report that in advanced disease (CD4 counts